Weight-related bullying in schools: a review of school anti-bullying policies - Amanda Hughes; Elisabeth Grey; Alice Haigherty; Fayth Shepherd; Fiona Gillison; Georgie MacArthur; Caoimhe Gowran; Rebecca Langford (BMC Public Health)
Abstract Introduction Weight is reported to be the most common target for bullying at school - far more common than other targets such as ethnicity, religion or sexual orientation. Research suggests weight bias and stigma - including negative beliefs, attitudes and discriminatory behaviours related to a person’s weight - is prevalent in educational settings among both pupils and staff. Most schools have anti-bullying policies. Best practice recommendations advise policies should explicitly identify forms of unacceptable behaviour, such as racism or homophobia. We conducted an audit of secondary schools in southwest England to determine if/how they mention weight-related bullying in their policies, and whether this differs by school-level factors. Methods We obtained lists of all secondary mainstream state, private, and special schools in seven local authorities and downloaded anti-bullying policies from their websites. Policies were searched for key words related to weight and size. We also recorded whether policies mentioned appearance or other key targets for bullying, such as race, religion, sexuality etc. We obtained school level data including size, gender mix, academic performance and quality ratings. Results From 255 schools with an available bullying or behaviour policy, only 6.7% specifically mentioned weight-related bullying. Just under half (48.6%) mentioned bullying in relation to appearance. Bullying was most often mentioned in relation to race/ethnicity (94.5%), sexual orientation (93.3%), gender (85.9%), religion (84.9%) or gender identity (67.5%). Private schools (N = 40) were more likely to mention weight-related bullying (17.5%) than mainstream state schools (N = 148, 6.1%). No special schools, whether state (N = 41) or private (N = 26), mentioned weight-related bullying in their policies. There was no strong evidence that other school characteristics made a difference, but small numbers limited statistical power of these comparisons. Conclusion There is a significant mismatch between the prevalence of weight-related bullying in schools and its representation within school anti-bullying policies. Some types of school are more likely than others to mention weight-related bullying in their policies. We recommend that schools explicitly recognise weight-related bullying in their anti-bullying policies and explore how to support staff and pupils to take action.